Comparison of the Diagnostic Performance of Ultrasound-Based Thyroid Imaging Reporting and Data System (TIRADS) Classification with American Thyroid Association (ATA) Guidelines in the Prediction of Thyroid Malignancy in a Single Tertiary Center in Manila - Gacayan, Ryan James; Kasala, Ruben; Puno-Ramos, Ma. Patricia; Mojica, Dondee; Castro, Ma. Krisha (Journal of the ASEAN Federation of Endocrine Societies, 2021)
Objective. To compare the diagnostic performance of American College of Radiology-Thyroid Image Reporting and Data Systems (ACR-TIRADS) and the American Thyroid Association (ATA) guidelines on screening for thyroid malignancy. Methodology. A cross-sectional criterion-referenced study involving Filipino patients with thyroid nodules, 18-80 years old, who underwent ultrasound guided fine needle aspiration biopsy at the Thyroid Clinic of The Medical City from July to December 2019. The ACR-TIRADS and the ATA guidelines were compared for 197 nodules. Standard diagnostic parameters were calculated, namely sensitivity, specificity, PPV, NPV, positive and negative likelihood ratios and overall accuracies. Results. The risks of malignancy were 15% and 22% for TIRADS 4 and 5 respectively. For ATA guidelines, it’s 2%, 20%, and 15% for nodules with low, intermediate, and high suspicion respectively. The sensitivity, specificity, PPV, NPV, and accuracy of the American College of Radiology Thyroid Imaging Reporting and Data System (ACR TIRADS) in relation to Fine Needle Aspiration Cytology (FNAC) is 100%, 52.2%, 16.5%, 100%, and 56.4% respectively. For the American Thyroid Association (ATA) guidelines it is 88.2%, 57.8%, 16.5%, 98.1%, and 60.4% respectively. Conclusion. The ACR TIRADS classifications appears to be more sensitive than the ATA classification. The ATA guidelines prove to be a more specific test. Each tool has its unique advantages and disadvantages. Therefore, clinicians must use these tools with utmost vigilance to avoid over or under diagnosis and to avoid unnecessary thyroid nodule biopsies.